The Attitudes of University Students towards Today’s World Affairs - Dönmez, Yasin (Journal of History Culture and Art Research, 2017)
This study was conducted to evaluate the attitudes of university students towards today’s world affairs in terms of some variables. 560 senior grade students participated in the study. The students were studying at Karabük University, Faculty of Literature in 2015-2016 Academic Year. The Review Model was used in the present study, and the “Today’s World Affairs Attitude Scale” was used as the data collection tool. Frequencies, percentages, arithmetic averages, Independent Samplings t-Test, and One-Way Variance Analysis (ANOVA) were used in the analyses of the data. It was concluded in the study that the attitudes of university students on today’s world affairs are positive and high. In addition, it was also determined in the present study that the attitudes of the students who participated in the study on today’s world affairs vary according to the gender variable at a significant level, and do not vary according to the programs in which they are studying.